Colony and Single Cell Level Analysis of the Heterogeneous Response of Cryptococcus neoformans to Fluconazole - Altamirano, Sophie; Simmons, Charles; Kozubowski, Lukasz (Frontiers in Cellular and Infection Microbiology, 2018)
Cryptococcus neoformans is a human fungal pathogen that can cause fatal meningitis in immunocompromised individuals. Fluconazole (FLC) is a fungistatic drug administered to treat cryptococcosis. When exposed to the inhibitory concentration of FLC, C. neoformans exhibits heteroresistance where a small subpopulation of cells develops into FLC-resistant colonies. FLC-resistant cells are aneuploids with regard to specific beneficial chromosomal regions. Factors underlying the potential for only certain C. neoformans cells in a genetically isogenic population to become FLC-resistant are unknown. In this study, we systematically examine the heterogeneous response of C. neoformans to FLC at a colony and individual cell level. We find that the heterogeneity in response to FLC is reflected by variable diminishment of the ergosterol at the plasma membrane. A population of C. neoformans spread on a semi-solid medium displays two types of outcomes following FLC exposure. The first outcome is colonies consisting of non-resistant cells (survivors). The size of colonies consisting of survivors ranges from a few cells to visible colonies, which reflects intrinsic phenotypic heterogeneity of the C. neoformans population. The second outcome is FLC-resistant cells forming colonies of sizes significantly larger as compared to colonies made of survivors. We propose a model that describes how a distribution of these types of cellular responses within a population changes depending on FLC concentration and factors that influence the rate of cellular growth including temperature, media type, growth phase, and the age of cells. Our findings highlight a complex nature of the response to a fungistatic drug and provide insights that may help to optimize FLC therapy.